PERAN DISIPLIN DALAM MENINGKATKAN KINERJA PEGAWAI ( STUDI PENELITIAN PADA KANTOR KELURAHAN SUNGAI KELEDANG SAMARINDA SEBERANG ) - Bud, Budi (PREDIKSI, 2016)
ABSTRACTÂ BUDI. Role of Discipline in Improving Employee Performance (Research Study In Office Samarinda Seberang Sungai Keledang) under the guidance of Mrs. Dra. Hj.Nanik Pujiastuti, M.Si as a mentor I and Mr. Drs.Damai Darmadi , M.SiThe purpose of this study was to determine the causal relationship between the variables disciplines with variable performance of employees at the Office of Samarinda Seberang Sungai Keledang, to solve a problem that has been the author pointed out earlier, and to verify whether the hypothesis can be accepted or rejectedThis type of research conducted by the author are Verivikatif, a study that you want to know and find the relationship between the two variables by analyzing the results of research using census method.That there is a positive relationship between the variables Discipline on Employee Performance At River Village Office Keledang Samarinda Seberang. It is from the analysis of the data by the formula coefficients Spearman Rank Correlation (r s) where r s count obtained for 0.578 was greater when compared with the price of r s theoretical (table prices are critical r s) at the 95% confidence level for N = 26, ie 0.329.The writer suggested that the hypothesis could be accepted as true. This is evident from the results of testing the hypothesis with t test formula, obtained t calculate equal to 3.468 which was greater when compared to the price table t (Table prices are critical t) at a rate of 95% for N - 2 (26-2) = 24 is 1.711, meaning that the writer suggested the hypothesis can be accepted as trueÂ Â